TI_GERICHTE 12.2015.13 vom 20. Juli 2015 , Riconoscimento e exequatur di sentenza estera - provvisionale ex art. 539 CPP/It - TI Tribunale d'appello (2015)
Riconoscimento e exequatur di sentenza estera - provvisionale ex art. 539 CPP/It